Wars, internal conflicts, and political order : a Jewish democracy in the Middle East - Barzilai, Gad. (Albany : State University of New York Press, 1996)
Annotation This is the first comprehensive research study to analyze and explain the influence the prolonged Arab-Israeli conflict has had on Israel. It focuses on the manner in which all of the Israeli-Arab wars since 1949, including the Intifada and the Gulf War, have affected state and society in Israel. In addition, it examines the influences of other, more limited Israeli military operations.
The Power Illusion Smashed and National Security Affairs (Partly) DemocratizedWar of Initiative and Political Polarization -- Israeli Society and Politics during the Gulf War -- The Inter-Communal Conflict of the Intifada and the Israeli Regime (1987-93) -- The Long-Term Effects of Wars and the Emergency Situation -- Final Conclusions: Establishing a Civilian Society -- Back Matter -- Notes -- Bibliography -- Subject Index -- Name Index -- Back Cover
Includes bibliographical references (pages 277-289) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Israel -- History, Military; Arab-Israeli conflict; War and society -- Israel; Politics and war; Democracy -- Israel; Conflit israélo-arabe.; Guerre et société -- Israël.; Politique et guerre; HISTORY; Arab-Israeli conflict; Democracy; Politics and war; War and society; Israel; Military history